Infaunal augurs of the Cambrian explosion: An Ediacaran trace fossil assemblage from Nevada, USA. Issue 4 (3rd April 2020) - Tarhan, Lidya G.; Myrow, Paul M.; Smith, Emily F.; Nelson, Lyle L.; Sadler, Peter M.
Abstract: Morphologically complex trace fossils, recording the infaunal activities of bilaterian animals, are common in Phanerozoic successions but rare in the Ediacaran fossil record. Here, we describe a trace fossil assemblage from the lower Dunfee Member of the Deep Spring Formation at Mount Dunfee (Nevada, USA), over 500 m below the Ediacaran–Cambrian boundary. Although millimetric in scale and largely not fabric‐disruptive, the Dunfee assemblage includes complex and sediment‐penetrative trace fossil morphologies that are characteristic of Cambrian deposits. The Dunfee assemblage records one of the oldest documented instances of sediment‐penetrative infaunalization, corroborating previous molecular, ichnologic, and paleoecological data suggesting that crown‐group bilaterians and bilaterian‐style ecologies were present in late Ediacaran shallow marine ecosystems. Moreover, Dunfee trace fossils co‐occur with classic upper Ediacaran tubular body fossils in multiple horizons, indicating that Ediacaran infauna and epifauna coexisted and likely formed stable ecosystems.